Anatomy Live Performance and the Operating Theatre - Bleeker, Maaike (MediaMatters, 2008)
Gross anatomy, the study of anatomical structures that can be seen by unassisted vision, has long been a subject of fascination for artists. For most modern viewers, however, the anatomy lesson hardly seems the proper breeding ground for the hybrid workings of art and theory. We forget that, in its early stages, anatomy pursued the highly theatrical spirit of Renaissance science, as painters such as Rembrandt and Da Vinci and medical instructors shared audiences devoted to the workings of the human body. Anatomy Live turns our modern notions of the dissecting table on its head - using anatomical theatre as a means of obtaining a fresh perspective on representations of the body, conceptions of subjectivity, and own knowledge about science and the stage. Critically dissecting well-known exhibitions like Body Worlds and The Visible Human Project and featuring contributions from a number of diverse scholars, Anatomy Live is not to be missed by anyone with an interest in this engaging intersection of science and artistic practice. This title is available in the OAPEN Library - http://www.oapen.org.